Enhancing Lifestyle Counselling Targeted at Weight Management for Patients on Antipsychotics in a Community Mental Health Team: A Quality Improvement Project - Madhulika Joglekar; Keya Patel; Sungjun Park; Peeyush Roy; Olubunmi Olure (BJPsych Open)
Aims: The association between antipsychotic medication and weight gain is widely recognised. The Royal College of Psychiatrists’ Positive Cardiometabolic Health Resource recommends lifestyle counselling as per the National Health Service Eat Well and Live Well guides, and the United Kingdom Chief Medical Officers’ Guidance on physical activity, to promote positive lifestyle behaviours and a healthy BMI in patients with psychosis. Owing to a lack of educational resources for healthcare professionals, patients at a Community Mental Health Team in Kent were not exposed to thorough lifestyle counselling. This project aimed to improve staff awareness and confidence with respect to the recommended dietary and physical activity counselling guidelines by 80% within a four-month period.